Application of LC-MS/MS Method for Evaluating Rosuvastatin Affinity with OATP1B1 and OATP2B1 in vitro - Zhang1, Zhi-Yu; Li2, Quan-Sheng; Si2, Duan-Yun; Yi2, Xiu-Lin; Liu2, Chang-Xiao (Asian Journal of Chemistry, 2014)
Drug-drug interaction is one of the most important preclinical investigation directions. It may have serious impact on drug absorption, distribution and elimination through membrane transporters. Liquid chromatography/Tandem mass spectrometry (LC/MS/MS) could be used to investigate drug-drug interaction in vitro. A sensitive LC/MS/MS method was established for quantification of rosuvastatin in HEK293 and S2 cell lysates. Internal standard (IS) was indapamide. Detection mode was positive electrospray ionization. The lower limit of quantification (LLOQ) was 0.05 ng/mL. The affinity of rosuvastatin with organic anion-transporting polypeptides 1B1 and 2B1 (OATP1B1 and OATP2B1) was investigated through uptake experiment. All cell samples were precipitated with methanol. Analytes were separated by reversed-phase chromatography and analyzed by Tandem mass spectrometry using m/z 482.2/ 258.1 for rosuvastatin and m/z 366.1/132.1 for indapamide. Rosuvastatin uptake was saturable with Km value of 11.70 and 5.98 μM for OATP1B1 and OATP2B1. Rosuvastatin could be used as a good probe for studying membrane transporter activity and drug-drug interaction through LC/MS/MS method.